Penyuluhan Hukum Hak Asasi dalam Upaya Pencegahan Perkawinan pada Usia Anak di Lingkungan Sekolah - Evendia, Malicia; Saleh, Ahmad; Riananda, Martha (Universitas 45 Surabaya, 2025)
Children play an important role in determining the quality of a nation's civilization. It is no surprise that preparing the next generation is an important dimension for state administrators. Guarantees for the protection of children's rights are not only regulated in the Indonesian constitution, but also reinforced in Law No. 23 of 2002 in conjunction with Law No. 17 of 2016 concerning Child Protection. Even Law No. 39 of 1999 on Human Rights contains provisions that children's rights are human rights and that for their benefit, children's rights are recognized and protected by law even from the moment of conception. Various parties have the obligation and responsibility to guarantee the fulfillment of these children's rights, starting from the smallest institutions, namely the family, community, village/sub-district government, sub-district, regency/city government, provincial government, and the government. One form of protection for children is by preventing child marriage. This community service activity aims to educate the community, especially students in schools, about children's rights. This is because the protection of children's human rights is regulated in various laws and regulations in Indonesia, including government efforts to prevent child marriage. It is important for students to understand this so that they can avoid marriage at a young age. This activity is a solution to reduce the number of child marriages. Therefore, the target audience for this activity is students. The activity held at YP UNILA High School in Bandar Lampung. The methods used in this activity will be lectures, and discussions.